Institutional Repositories and their Role in Knowledge Management: A Study of PAU Repository - Kumar, Sanjeev (Journal of Agricultural Extension Management, 2021)
Higher educational institutions, particularly agricultural universities, have a tripartite mandate which includes teaching, research, and extension. Open access initiatives have resulted in the growth and development of repositories where researchers can share their work for more visibility and impact. Institutional output can be better preserved and widely shared through institutional repositories. Librarians have better skills in managing knowledge; thus, collaborating with IT professionals can play a crucial role in managing and disseminating an institution’s research output. In today’s time, librarians have also involved themselves in assisting their organizations in demonstrating researchers and faculty impact of their research using conventional and alternative metrics. This article discusses the concept of knowledge management, institutional repositories, and their role as a green route to publication and disseminating institutional knowledge with particular reference to PAU repositories’ structure, growth, and development. It is an exploratory study taking into account the repository’s genesis, growth, and development. This study helps understand the concept of knowledge management and institutional repositories.